Caracterização de argamassas históricas: estudo de caso de uma residência localizada na Palma – município de Caicó/RN - Medeiros, Baraklein de (Universidade Federal Rural do Semi-Árido, 2019)
Historical buildings carry significant characteristics with regard to their materials, architecture, and historical and cultural values, so heritage must be decorated and consecrated for future generations to have access to the stories therein. However, in order to care for, restore and conserve an old building, it is necessary to know its first fruits, the form of construction and the components used in its manufacture, since the restoration of these buildings, when made with non-compatible materials, can irreparable damage. As with other building components, cladding mortar requires special care, as it is responsible for protecting and cladding buildings against weathering and aggressive agents in general. Old coatings are generally known to be more fragile, as they were generally made from lime and sand, and in some cases with the addition of pozzolanic or organic materials. . Based on this assumption, the present work aimed to characterize the mortars of historical coating of a residence located in Palma, Caicó Municipality in Rio Grande do Norte. For this purpose, site visits were carried out for visual studies, photographic records, sketching and sampling of various points of the building in order to characterize the mortar through technical analysis and laboratory tests. With the samples taken to the laboratory, it was possible to perform absorption test, visual, chemical and particle size analysis. Based on the results, it was found that lime was the binder used throughout the building, and that virtually the same binder: aggregate ratio trace was used in the construction, with the 1:8 trace being used in 8 of the 9 samples, and only a 1:7 used in one of the samples. In addition to other factors, it was also found that the aggregate most used in the mortar was the average sand.
Monografia
Keywords: Construções históricas; Argamassas antigas; Caracterização das argamassas; Argamassa a base de cal; Historical constructions; Old Mortars; Mortars characterization; Lime based mortar; ENGENHARIAS::ENGENHARIA CIVIL